Simultaneous Determination of Vancomycin, Cefoperazone, Sulbactam, and Ceftriaxone Antibiotics by Capillary Electrophoresis with Capacitively Coupled Contactless Conductivity Detection (CE-C4D) - Anh, Kieu Van; Nhi, Dao Yen; Lam, Vu Tung; Quan, Le Duc; Hao, Tran Thi My; Anh, Hoang Quoc; Thuong, Nguyen Thi Kim; Dung, Le Duc; Mai, Pham Thi Ngoc; Huong, Nguyen Thi Anh (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 3DO - 10.25073/2588-1140/vnunst.5535, 2023)
Combination drugs including antibiotics are frequently used for additional therapeutic effects. This fact raises the need for effective methods to simultaneously determine antibiotics of different classes. In this study, four antibiotics including vancomycin, cefoperazone, sulbactam, and ceftriaxone were determined simultaneously by capillary electrophoresis with capacitively coupled contactless conductivity detection (CE-C 4 D). The analytical conditions including effective length of silica capillary, background electrolyte solutions, separation voltages, and injection modes are investigated. The selected analytical conditions were: silica capillary (internal diameter 50 μm, total length 60 cm, effective length 30 cm); background electrolyte solution 10 Mm L-arginine/acetic acid (pH 9.2); separation voltage +17 kV; siphoning hydrodynamic sample injection at 10 cm height for 20 s. Limits of detection (LOD) of vancomycin, cefoperazone, sulbactam, and ceftriaxone were 2.0 ppm, 1.5 ppm, 1.0 ppm, and 2.0 ppm, respectively. Good linearity (R 2 > 0.999) was achieved for all the target compounds until concentrations as high as 100 ppm. Analytical results of blank-spike samples indicate acceptable recovery (97.5% - 100.4%) and repeatability (RSD: 0.99% - 3.04%). The validated method has been applied to determine these four antibiotics in several pharmaceutical samples. Good agreement between results of our method and the LC-MS/MS method, suggesting CE-C 4 D is a reliable and cost-effective method in pharmaceutical analysis.